Investigation of the performance and thermal decomposition of MgO and MgO-SiO 2 formulations - Sonat, Cem (2017)
The use of magnesium oxide (MgO) as the key reactive component within hydraulic binder systems has been reported in many studies. This study investigated the strength and microstructural development of MgO and MgO-SiO2 binder systems under different curing conditions. Concrete samples, whose binder component consisted of only MgO or MgO-SiO2 were subjected to ambient and carbonation curing conditions for 56 days. The compressive strength results were supported with microstructural analysis performed via XRD, TG/DTG and FESEM. While the formation of brucite within MgO samples led to limited strength under ambient conditions, MgO-SiO2 samples demonstrated a steady strength development due to the formation of M-S-H. Incorporation of carbonation curing enhanced the mechanical performance of both systems, enabling rapid strength development that reached up to 77 MPa at 7 days. This increase in strength was associated with the densification of microstructure via the formation of Mg-carbonates, which were assessed via thermal analysis.